High active amorphous Co(OH)2 nanocages as peroxymonosulfate activator for boosting acetaminophen degradation and DFT calculation - Juanjuan Qi; Juzhe Liu; Fengbin Sun; Taobo Huang; Duan, Jun; Liu, Wen (Chinese Chemical Letters, 2021)
Acetaminophen (ACE) is commonly used in analgesic and antipyretic drug, which is hardly removed by traditional wastewater treatment processes. Herein, amorphous Co(OH)2 nanocages were explored as peroxymonosulfate (PMS) activator for efficient degradation of ACE. In the presence of amorphous Co(OH)2 nanocages, 100% of ACE removal was reached within 2 min with a reaction rate constant k1 = 3.68 min−1 at optimum pH 5, which was much better than that of crystalline β-Co(OH)2 and Co3O4. Amorphous materials (disorder atom arrangement) with hollow structures possess large specific surface area, more reactive sites, and abundant vacancies structures, which could efficiently facilitate the catalytic redox reactions. The radicals quenching experiment demonstrated that SO4− radicals dominated the ACE degradation rather than OH radicals. The mechanism of ACE degradation was elucidated by the analysis of degradation intermediates and theoretical calculation, indicating that the electrophilic SO4− and OH tend to attack the atoms of ACE with high Fukui index (f −). Our finding highlights the remarkable advantages of amorphous materials as heterogeneous catalysts in sulfate radicals-based AOPs and sheds new lights on water treatment for the degradation of emerging organic contaminants.
Keywords: Acetaminophen (ACE); Amorphous Co(OH); DFT calculation; Intermediates; Peroxymonosulfate (PMS)